ADOPSI TERHADAP INOVASI: KAJIAN KONSEPTUAL IMPLEMENTASI PROGRAM LAKU PANDAI PADA LAYANAN BRILink - Dikdik Tandika; Lufthia Sevriana (Universitas Islam Bandung, 2017)
Financial inclusive is a part of three strategies to achieve economy welfare through poverty alleviation, two others strategies are social inclusion and economic inclusion. So far there are only two alternatives of financial services for Indonesian far corners area, they are financial service through cooperative and loan sharks. Those condition causing unabsorbed society fund potential by Bank. At the end of march 2015, Financial Service Authority (OJK) inaugurate financial service innovation such as “Laku Pandai” Program as Banking solution to absorp society fund potential . BRILink as “Laku Pandai” Program, were introduced in 2013 and together with OJK as policy maker of financial inclusive program. This research will determine innovation characteristics at the user of BRILink services based on five innovation characteristics, they are: Relative advantage, Compatibility, Complexity, Trialability, Observability.